Kazimierz quarry – protection of cultural landscape - Michalska, Grażyna; Niedźwiedź, Jan (Budownictwo i Architektura / Civil and Architectural Engineering, 2010)
The article concerns for question of protection of Kazimierz quarry, winning limestone. It is located near Kazimierz Dolny at Vistula River. It characterize history of Kazimierz quarry reaching XIV century as well as the description of landscape and geological values. Particular attention concerns necessity and ways of protection of quarry as classic example cultural landscape.